The Role of the Nganjuk KPU Election Smart House in Enhancing Students Political Literacy and Democratic Understanding - RENGGA YUDHA SANTOSO; Erik Satrya Pratama Wisnu Wardana; Kri Pratama (CV. Civiliza Publishing, 2026)
Democracy education in Indonesia still faces challenges in improving understanding of elections, especially among students. The Nganjuk KPU Election Smart House (RPP) is one of the efforts to overcome this problem by providing a place for democracy education for students. This study aims to evaluate the role of the Nganjuk KPU RPP in improving understanding of democracy and voter participation among students. This research method uses a qualitative approach with case studies on activities carried out at the RPP KPU Nganjuk, which involves interviews with students and direct observation of the activities that take place. The results indicate that the RPP KPU Nganjuk is effective in enhancing students understanding of democracy and elections, as evidenced by positive feedback rates of 70–85% across eight participating schools, active student engagement reflected in 12–15 questions asked per session, and interview responses indicating increased civic awareness. Nevertheless, challenges remain, including limited facilities and varying prior knowledge among students from urban and rural areas.